PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITAS, DAN LEVERAGE TERHADAP KEINFORMATIFAN LABA DENGAN KINERJA LINGKUNGAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia pada tahun 2014-2017) - Mutiara Ihdina; Afifudin Afifudin; Junaidi Junaidi (Universitas Islam Malang, 2019)
ABTRACTThe purpose of this study is to examine the effect of disclosure of corporate social responsibility, profitability and leverage on informational informativeness with environmental performance as a moderating variable. The sample in this study were 15 mining companies listed on the Indonesia Stock Exchange. In this study the sampling technique used purposive sampling. The analysis technique used in the research is multiple regression analysis. The results of this study indicate that corporate social responsibility and profitability have a significant effect on profit informativeness and leverage has no significant effect on earnings informativeness. Environmental performance does not moderate corporate social responsibility towards informational profitability and environmental performance to moderate profitability, leverage against profit informativeness.Keywords: Corporate Social Responsibility, Profitability, Leverage, Informative Profit.